2011
DOI: 10.1108/13595471111185747
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Psychological Therapies for people with learning disabilities

Abstract: Purpose -This paper considers the applicability of the Improving Access to Psychological Therapies (IAPT) initiative in meeting the mental health needs of people with learning disabilities.Design/methodology/approach -The author considers the nature of the IAPT service, the potential benefits, the potential barriers and how local services could be better adapted to meet the needs of people with learning disabilities.Findings -Although the IAPT service is well established for the mainstream population, for peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…87 Median MOAS scores were a little lower than those recorded in a trial of neuroleptic drug treatment for aggressive behaviour in people with intellectual disabilities, which reported a median [interquartile range (IQR)] MOAS score of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) at baseline in the placebo-treated group, and a dramatic fall (to a median score of ~3: considerably lower than the present participants) during subsequent weekly assessments under placebo treatment. 115 There is a limit to the extent of challenging behaviour that could in principle be observed in this study because most of the services from which participants were recruited would often exclude individuals who are overtly challenging.…”
Section: Challenging Behaviourmentioning
confidence: 69%
See 2 more Smart Citations
“…87 Median MOAS scores were a little lower than those recorded in a trial of neuroleptic drug treatment for aggressive behaviour in people with intellectual disabilities, which reported a median [interquartile range (IQR)] MOAS score of 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) at baseline in the placebo-treated group, and a dramatic fall (to a median score of ~3: considerably lower than the present participants) during subsequent weekly assessments under placebo treatment. 115 There is a limit to the extent of challenging behaviour that could in principle be observed in this study because most of the services from which participants were recruited would often exclude individuals who are overtly challenging.…”
Section: Challenging Behaviourmentioning
confidence: 69%
“…7 There are many barriers that limit access to psychological therapies for people with intellectual disabilities, including social restrictions, communication problems, challenging behaviours, a failure of general practitioners to recognise mental health problems, and exclusion criteria operated by specialist mental health services. 7,8 However, a further problem is that the necessary research on effectiveness of psychological therapies for this population is still at a rudimentary stage. It is only recently that CBT has been adapted for people with intellectual disabilities.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whilst these are all indications of positive local service developments, rather than a national drive, service developments for this client group appear dependant on the commitment of local IAPT services and commissioning bodies (Leyin, 2011). A recent large scale study indicated that some IAPT services may even explicitly exclude this client group (Chinn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prout & Browning () in their review of the effectiveness of therapies for this population conclude that both individual and group psychotherapeutic interventions such as CBT, imagery rehearsal therapy and anger management offer some degree of benefit as long as reasonable adaptations/adjustments are made to make the therapy accessible. The issue of ‘reasonable adjustment’ remains unclear as in our opinion, modifying an intervention to a large degree questions the evidence base for the intervention, an argument highlighted by Leyin (). It must also be noted that approaches such as CBT may not be suitable for all people with ID, particularly those with little or no language and have severe disabilities and high support needs (Sturmey ).…”
Section: Introductionmentioning
confidence: 99%